Acceptance and awareness regarding influenza vaccine among healthcare workers in a tertiary care centre, Kerala - Puliyakkadi, Safa; Kulankara, Rohini; Philip, Reo; Mathumkunnath Vijayan, Sajna; Vijayakumar, Arya (International Journal Of Community Medicine And Public Health, 2023)
Background: The seasonal Influenza is a contagious respiratory illness. The most important step in preventing flu is to get a flu vaccination each year along with everyday preventive actions. The objective of this research was to study the acceptance and awareness of Influenza vaccine among health care workers of a tertiary care centre, Kerala and to explore the preventive practices. Methods: This study was a hospital based cross sectional study conducted among 204 health care workers in a tertiary centre in Kerala. A simple random sampling technique was adopted. Data was collected using self-administered pretested semi structured questionnaires. Results: 165 (80.9%) are aware of the Influenza vaccine while 39 (19.1%) are not aware of the Influenza vaccine. 30 (14.7%) has received at least one dose of Influenza vaccine in last five years while 174 (85.2%) has not received the vaccine. 161(78.9%) says they are willing to get vaccinated against Influenza while 43(21.1%) are not willing to get vaccinated. Conclusions: Even though there is good awareness about Influenza vaccine, the number of vaccine recipients is less than ideal. However, majority are willing to take Influenza vaccine in the future which shows good acceptance.